A mediation analysis of Autistic-like traits and gaming motivations on problem gaming symptoms: Are the effects of social and escape motives the same? - Jake D. Slack; Ben Mctigue; Heather Mackenzie; Mal Flack; Kim M. Caudwell (Addictive Behaviors Reports, 2025)
There are higher rates of video game use and potentially gaming disorder among individuals with autism spectrum disorder (ASD). However, the association between subthreshold autistic-like traits (ALTs) and gaming behaviour remains relatively unexplored. The present study assessed whether gaming motives may mediate the relationship between ALTs and gaming disorder symptoms. A total of 378 (Mage = 31.41, SD = 8.84) respondents completed an online survey, which included measures of gaming disorder symptoms, gaming motives, and ALTs. Findings indicated that social and escape motives mediated relationship between ALTs and gaming disorder symptoms, after controlling for time gaming. However, ALTs displayed a negative association with social motives and a positive association with escape and both social and escape motives were positively associated with gaming disorder symptoms. These findings indicate that individuals with higher levels of ALTs may game primarily for escape from real-life challenges and less so for social reasons, potentially exacerbating problem gaming symptoms. These results underscore the importance of understanding gaming motives, as they can inform targeted interventions for reducing problematic gaming. This study contributes to the growing body of literature on gaming behaviour, emphasising the need for motives to be considered in educational and problem gaming support initiatives.